Correction: Changes in macrocyclic aromaticity and formation of a charge-separated state by complexation of expanded porphyrin and C60. Issue 3 (5th January 2021) - Cha, Won-Young; Ahn, Ahreum; Kim, Taeyeon; Oh, Juwon; Ali, Rashid; Park, Jung Su; Kim, Dongho
Abstract : Correction for 'Changes in macrocyclic aromaticity and formation of a charge-separated state by complexation of expanded porphyrin and C60 ' by Won-Young Cha et al., Chem. Commun., 2019, 55, 8301–8304, DOI: ; 10.1039/C9CC03928G .